2000
DOI: 10.1007/s11627-000-0050-2
|View full text |Cite
|
Sign up to set email alerts
|

A shoot regeneration protocol effective on diverse genotypes of sunflower (Helianthus annuus L.)

Abstract: We describe a protocol, and several experiments that helped lead to its development, for sunflower regeneration. Important factors for sunflower regeneration were explant age, cytokinin type and concentration, basal medium, and explant source. We could not induce shoot regeneration from the explants derived from mature tissues including leaf, petiole, and stem. However, use of juvenile explants such as embryo meristem and primordial leaf tissues allowed routine regeneration of 17 different sunflower genotypes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…When we compared the three media, (MS, B5 and WPM), the contents of phosphorus and calcium were similar, while the content of nitrogen was different. The total nitrogen content in WPM medium (14.7 M) was much lower than that in MS (60.03 M) and B5 (27.0 3 M) (Shi et al, 2000). In this study, it appears that the content of total nitrogen might be an important factor that affected shoot regeneration of P. amurense.…”
Section: Effect Of Basal Medium On Shoot Regenerationmentioning
confidence: 57%
“…When we compared the three media, (MS, B5 and WPM), the contents of phosphorus and calcium were similar, while the content of nitrogen was different. The total nitrogen content in WPM medium (14.7 M) was much lower than that in MS (60.03 M) and B5 (27.0 3 M) (Shi et al, 2000). In this study, it appears that the content of total nitrogen might be an important factor that affected shoot regeneration of P. amurense.…”
Section: Effect Of Basal Medium On Shoot Regenerationmentioning
confidence: 57%
“…Fertile plant regeneration (Shin et al, 2000) has been also observed from embryo meristem and primordial leaf tissues. However, the plant heights of their in vitro regenerated genotypes were higher (142-263 cm) than genotypes used in this study (43.33-102.67 cm).…”
Section: Resultsmentioning
confidence: 96%
“…The process of sunflower regeneration is affected by many factors, either alone or in combination. These include genotype (Dağüstü, 2002;Paterson, 1984;Power, 1987), composition of culture medium (Shin et al, 2000), the age of explant (Dağüstü, 2002;Knittel et al, 1991;Paterson and Everett, 1985;Shin et al, 2000); explant type (Ceriani et al, 1992;Dağüstü, 2002;Shin et al, 2000), and environmental factors (Fiore et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, para a bromélia Tillandsia eizii, a idade do explante, 21 e 84 dias, não afetou significativamente as variáveis % de explantes com brotos e número de brotos/explante (PICKENS et al 2006). O sucesso na propagação de explantes mais jovens pode ser atribuído à existência de muitas células meristemáticas e indiferenciadas que apresentam crescimento rápido, o que é essencial para iniciar as culturas (SHIN et al, 2000;BISPO et al, 2007). Quanto à variável comprimento médio de brotos, explantes com 40 dias de idade, independente da concentração de regulador aplicada, produziram brotos maiores, 7,80 e 5,99mm, não diferindo significativamente apenas do caule com 20 dias na concentração de 1,30μM de ANA.…”
Section: Resultsunclassified